PLASMAPHERESIS FOR THYROTOXICOSIS: EXPERIENCE FROM A MALAYSIAN ACADEMIC MEDICAL CENTRE - Lim, Quan Hziung; Hee, Nicholas Ken Yoong; Sarvanandan, Tharsini; Ooi, Ying Guat; Khoo, Jun Kit; Lim, Lee Ling; Ratnasingam, Jeyakantha; Vethakkan, Shireene Ratna (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Plasmapheresis is a therapeutic option for patients with severe thyrotoxicosis as a bridging therapy to urgent thyroidectomy, or when conventional antithyroid medications are ineffective, contraindicated, or cause adverse reactions. This retrospective study aims to describe the indications of plasmapheresis, clinical outcomes, and the periprocedural thyroid hormone level changes among patients with thyrotoxicosis in our local setting. METHODOLOGY Electronic medical records of all patients who required plasmapheresis in thyrotoxicosis for various indications at Universiti Malaya Medical Centre from April 2022 to April 2025 were reviewed. Clinical outcomes were recorded, and periprocedural fT4 levels were tabulated. RESULT There was a total of 11 patients in the study – nine (81.82%) were females, with a mean age of 49.9 ± 22.2 years. Only five (45.45%) fulfilled criteria for thyroid storm, whereas four (36.36%) required urgent thyroidectomy for other reasons, two (18.18%) required urgent reversal of thyrotoxicosis for other surgeries. Five (45.45%) patients died - three of whom were due to thyroid storm, and two due to other concurrent acute illnesses. Four (36.36%) patients developed periprocedural complications including allergic reaction and tachyarrhythmias. Overall, each patient underwent an average of 3.72 ± 2.33 cycles of plasmapheresis, whereas the survivors required 4.17 ± 3.13 cycles to achieve their therapeutic goals. All patients used fresh frozen plasma for exchange, with an average of 1.3 ± 0.3 times total plasma volume. Over 33 cycles in between all patients, the average reduction of fT4 per liter of plasma exchanged was 2.26 ± 5.09 pmol/L, and the average percentage reduction of fT4 after each treatment was 11.0 ± 28.1 %. CONCLUSION Patients in thyrotoxicosis who require plasmapheresis usually have complex or severe diseases. Apart from currently recognised indications, another indication would be patients who require urgent lowering of thyrotoxicosis for other interventional procedures. There is a need for standardization of care to facilitate early recognition and timely implementation of this life-saving procedure.